Procesos biotecnológicos para la proliferación y enraizamiento in vitro de Hualtaco Laxopterygium huasango Spruce ex Engl., proveniente del bosque seco de la provincia de Loja - Conde Solano, Verónica Maribel (2015)
The plant micropropagation a useful tool for the conservation of threatened species, then through the techniques of in vitro culture can increase the number of individuals per unit area of any species subject to conservation. In this context micropropagationLoxopterygium huasango species Spruce ex Engl., It is proposed as an alternative plant propagation, since this technique allows a better understanding of physiological and environmental factors involved in the formation of adventitious organs, by in vitro propagation. From this perspective the present research was conducted "Biotechnological processes for in vitro proliferation and rooting Hualtaco Loxopterygium huasango Spruce ex Engl., from the dry forest in the province of Loja", the same that was to develop laboratory tests to disinfect seeds and explants field, seed germination in vitro, multiplication, sprouting and rooting of explants from plantlets in vitro, thus contributing to generate information for the establishment of protocols in vitro propagation of Loxopterygium huasango Spruce ex Engl. This research was conducted under the project: "Generation of protocols for in vivo and in vitro propagation of elite genotypes of native forest species and promising for reforestation in the southern region of Ecuador"into two phases: phase field and laboratory; the period from November 2013 to December 2014, the field phase corresponded to the collection of plant material in the sectors: Lucarqui - Bramaderos (Paltas county), International Bridge - Vizin (Macará county) and Limones (Zapotillo county); and the second phase was conducted in the Laboratory of Plant Micropropagationof the National University of Loja. The basal culture medium MS (Murashige and Skoog 1962) was used in all experiments, supplemented with various growth regulators. In the testseed disinfectionsodium hypochlorite (commercial chlorine) was used in three concentrations(25, 50 and 75%), with threeimmersion times(5, 10 and 15min), respectively, where 50% sodium hypochlorite for 5 minutes was the best treatment to control pollution.For disinfectionand in vitroexplantfieldimplantation, the collectionof plant materialwas performedinZapotillo, MacaraandcantonsPaltas, Disinfectionisperformed usingsodium hypochlorite (commercial chlorine) inthree concentrations(15, 20 and 25%) with twoimmersion times(5 and 10min), respectively; but none of thetreatmentstestedallowedpollution controlexplantsfield. For germinationin vitrothree methodsappliedscarification(without scarification, physicalandmechanical) with three concentrationsof AG3 (0; 0,5 y 1 mg/L), reachingthe highest percentage of77.78%germinationin the treatment withoutscarificationand adding1mg/L of AG3. Formultiplicationtests, sproutingand rooting in vitroexplants(shoot tip andnodal segments), in vitro germinated seedlings was used 4 to 5cm heightwith 1 to 2 knots, to obtainexplants. In thein vitromultiplicationtestthreecytokininsareused: benzylaminopurine(BAP), kinetin(KIN) andisopentiladenina(2ip), into twoconcentrations1 and 2mg/Lrespectively, cytokinin2ipresultinginconcentration of 1mg/Lthe best treatment. For in vitrosproutingcytokininBAPwere used.KINand2ipinconcentration of 1mg/L, supplemented withadeninesulfate 5 y 25 mg/L and coconut water0 to 20%, achievingthe best results with1 mg/L2ip+5 mg/Ladeninesulfateand 0% ofcoconut water. For in vitrorootingthreetestedauxins: naphthaleneacetic acid (ANA), indole aceticacid (AIA) andindolebutyricacid (AIB) at three concentrations(0,5; 1 and 1,5mg/L) respectively, the best resultsbeing achievedwith 1.5mg/LAIA,as it was ableto inducethe highest number ofrootsformedper explant.